FAKTOR-FAKTOR YANG MEMPENGARUHI PENGHENTIAN PREMATUR ATAS PROSEDUR AUDIT: KONTROL KUALITAS SEBAGAI VARIABEL PEMODERASI: THE DETERMINANTS OF PREMATURE TERMINATION OF AUDIT PROCEDURES: QUALITY CONTROL AS A MODERATING - Rahayu, Rahayu; Hardi, Hardi; Hariadi, Hariadi (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2024)
In controlling and improving the caliber of organizational services, audit is essential, especially when it comes to reducing potentially dangerous dangers. However, ending audit processes too soon might lower audit quality and increase the chance of mistakes that could be harmful to the company. With quality control acting as a moderating variable, the objective of this research is to assess the effects of monitoring, audit risk, and professional ethics on the premature termination of audit procedures. Auditors working for public accounting firms in Pekanbaru and Medan made up the study's population; a questionnaire was used to choose 42 respondents. Data analysis was conducted using Partial Least Squares (PLS). The results reveal that audit risk positively and significantly effects the early termination of audit procedures, while supervision and professional ethics have a negative and significant impact. Furthermore, while quality control does mitigate the association between professional ethics and premature audit procedure termination, it does not moderate the relationship between supervisory activities and audit risk.